Sensor based time budgets in commercial Dutch dairy herds vary over lactation cycles and within 24 hours. - P R Hut; S E M Kuiper; M Nielen; J H J L Hulsen; E N Stassen; M M Hostens (PLoS ONE, 2022)
Cows from 8 commercial Dutch dairy farms were equipped with 2 sensors to study their complete time budgets of eating, rumination, lying, standing and walking times as derived from a neck and a leg sensor. Daily sensor data of 1074 cows with 3201 lactations was used from 1 month prepartum until 10 months postpartum. Farms provided data over a 5 year period. The final models (lactational time budget and 24h time budget) showed significant effects of parity, farm and calving season. When primiparous cows were introduced in the lactational herd, they showed a decrease in lying time of 215 min (95% CI: 187-242) and an increase in standing time of 159 min (95% CI: 138-179), walking time of 23 min (95% CI: 20-26) and rumination time of 69 min (95% CI: 57-82). Eating time in primiparous cows increased from 1 month prepartum until 9 months in lactation with 88 min (95% CI: 76-101) and then remained stable until the end of lactation. Parity 2 and parity 3+ cows decreased in eating time by 30 min (95% CI: 20-40) and 26 min (95% CI: 18-33), respectively, from 1 month before to 1 month after calving. Until month 6, eating time increased 11 min (95% CI: 1-22) for parity 2, and 24 min (95% CI: 16-32) for parity 3+. From 1 month before calving to 1 month after calving, they showed an increase in ruminating of 17 min (95% CI: 6-28) and 28 min (95% CI: 21-35), an increase in standing time of 117 min (95% CI: 100-135) and 133 min (95% CI: 121-146), while lying time decreased with 113 min (95% CI: 91-136) and 130 min (95% CI: 114-146), for parity 2 and 3+, respectively. After month 1 in milk to the end of lactation, lying time increased 67 min (95% CI: 49-85) for parity 2, and 77 min (95% CI: 53-100) for parity 3+. Lactational time budget patterns are comparable between all 8 farms, but cows on conventional milking system (CMS) farms with pasture access appear to show higher standing and walking time, and spent less time lying compared to cows on automatic milking system (AMS) farms without pasture access. Every behavioral parameter presented a 24h pattern. Cows eat, stand and walk during the day and lie down and ruminate during the night. Daily patterns in time budgets on all farms are comparable except for walking time. During the day, cows on CMS farms with pasture access spent more time walking than cows on AMS farms without pasture access. The average 24h pattern between parities is comparable, but primiparous cows spent more time walking during daytime compared to older cows. These results indicate a specific behavioral pattern per parameter from the last month prepartum until 10 months postpartum with different patterns between parities but comparable patterns across farms. Furthermore, cows appear to have a circadian rhythm with varying time budgets in the transition period and during lactation.